Keep it simple: Fast processing of periodic BCZT structures by combination of VPP and replica technique - Funk, Swantje; Wolf, Edwyn; Weichelt, Michelle; Martin, Alexander; Kakimoto, Ken-ichi; Fey, Tobias (Open Ceramics, 2025)
The replica technique has been widely used and continuously improved over the last decades. Pore size, distribution and strut geometry remain constrained by the polyurethane (PU) template. Periodic lattices are with special interest given to biomaterials and can be made by advanced replica technique, which offers precise control over the porosity of materials by using an adjustable 3D-printed template, the Kelvin cell. They were coated with a sol-gel Barium Calcium Zirconate Titanate (BCZT) based slurry achieving high d33 values of up to 33 ± 9 pC/N despite a porosity of 54 %. The upscaled approach of sol-gel BCZT synthesis was mandatory, as previous studies were not able to produce sufficient quantities. The findings indicate that the advanced replica technique enables the targeted adjustment of open and interconnected porosity in biomaterials, while BCZT exhibits favorable piezoelectric characteristics even for high porosities, further underscoring its potential in biomedical applications as a replacement/supplement to bioglass.
CRIS-Team Scopus Importer:2025-03-28
Keywords: Advanced replica technology; Bioceramics; Kelvin cells